1983
DOI: 10.1111/j.1464-410x.1983.tb03397.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Instability. is the Primary Defect in the Urethra?

Abstract: The urethral response to bladder filling has been studied by synchronous measurement of four points in the proximal urethra and bladder using microtip transducers. Twelve male patients with urodynamically proven bladder instability had falls in urethral closure pressure of 30 cm of water 3 s before the unstable detrusor contraction. There was a lack of awareness of the urethral relaxation, the sensation of urgency occurring only when the detrusor contracted. The suggestion is made that the sequence of events o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 5 publications
4
27
1
Order By: Relevance
“…If the balance between them is lost an involuntary opening of the urethra might occur. The urethral pressure fall that takes place immediately before the detrusor contraction in normal micturition is mimicked in overactive conditions [Hindmarsh et al, 1983;Petros and Ulmsten, 1993;Wise et al, 1993]. Findings in a recent study from our laboratory support an active role also for the bladder outlet and the urethra in the context of over activity.…”
Section: Introductionsupporting
confidence: 52%
“…If the balance between them is lost an involuntary opening of the urethra might occur. The urethral pressure fall that takes place immediately before the detrusor contraction in normal micturition is mimicked in overactive conditions [Hindmarsh et al, 1983;Petros and Ulmsten, 1993;Wise et al, 1993]. Findings in a recent study from our laboratory support an active role also for the bladder outlet and the urethra in the context of over activity.…”
Section: Introductionsupporting
confidence: 52%
“…Through the urethral detrusor facilitative reflex, an open bladder neck might induce unstable detrusor contraction or urge sensation during the straining condition. 25 If the bladder neck can be closed concomitantly during the pubovaginal sling procedure, the postoperative urgency or urge incontinence might disappear, as observed previously in patients with mixed incontinence who underwent colposuspension. 26 In some women with a nonfunctioning urethra and an acontractile detrusor, the sling cannot be tied very tightly, and the position of the bladder neck has to be elevated to a certain degree.…”
mentioning
confidence: 78%
“…It has been suggested that unstable detrusor contractions may be initiated from the bladder outlet region rather than from the detrusor itself [32,51]. Morphological changes, e.g., those seen in outflow obstruction caused by benign prostatic hyperplasia, are associated with unstable bladder contractions in 50%-70% of cases [53].…”
Section: Afferent Activity and "Unstable" Bladder Contractionsmentioning
confidence: 99%